Brill's Companion to the Reception of Aeschylus - Kennedy, Rebecca Futo (Brill's Companions to Classical Reception Ser, 2017)
"Contents" -- "Acknowledgements" -- "List of Figures" -- "List of Abbreviations" -- "Author Biographies" -- "Introduction: The Reception of Aeschylus" -- "Part 1 Pre-Modern Receptions" -- "Chapter 1 The Reception of Aeschylus in Sicily" -- "Chapter 2 The Comediansâ Aeschylus" -- "Chapter 3 Aristotleâs Reception of Aeschylus: Reserved Without Malice" -- "Chapter 4 Aeschylus in the Hellenistic Period" -- "Chapter 5 Aeschylus in the Roman Empire" -- "Chapter 6 Aeschylus in Byzantium" -- "Part 2 Modern Receptions" -- "Chapter 7 Aeschylus and Opera" -- "Chapter 8 Aeschylus in Germany" -- "Chapter 9 Inglorious Barbarians: Court Intrigue and Military Disaster Strike Xerxes, âThe Sick Man of Europeâ" -- "Chapter 10 Transtextual Transformations of Prometheus Bound in Percy Bysshe Shelleyâs Prometheus Unbound: Prometheusâ Gifts to Humankind" -- "Chapter 11 Aeschylus and Frankenstein, or The Modern Prometheus, by Mary Shelley" -- "Chapter 12 An Aeschylean Waterloo: Responding to War from the Oresteia to Vanity Fair" -- "Chapter 13 Form and Money in Wagnerâs Ring and Aeschylean Tragedy" -- "Chapter 14 Eumenides and Newmenides: Academic Furies in Edwardian Cambridge" -- "Chapter 15 The Broadhead Hypothesis: Did Aeschylus Perform Word Repetition in Persians?" -- "Chapter 16 Persians On French Television: An Opera-Oratorio Echoing the Algerian War" -- "Chapter 17 Aeschylusâ Oresteia on British Television" -- "Chapter 18 Orestes on Trial in Africa: Pasoliniâs Appunti per unâ Orestiade Africana and Sissakoâs Bamako" -- "Chapter 19 Reception of the Plays of Aeschylus in South Africa" -- "Chapter 20 In Search of Prometheus: Aeschylean Wanderings in Latin America" -- "Chapter 21 Avatars of Aeschylus: OâNeill to Herzog/Golder" -- "Chapter 22 The Overlooked Î¿á¼°ÎºÎ¿Î½Î¿Î¼Î¯Î± of Aeschylusâ Agamemnon and Stanley Kubrickâs The Shining".